Quilotórax bilateral asociado a linfoma no Hodgkin, folicular. Génesis del quilotórax - Mechán, Víctor (2011)
This is the story of a 50 year-old male subject with a 7-month illness characterized by myalgia, fatigue, and malaise. 5 months before being admitted to Dos de Mayo National Hospital (HNDM), he developed right pleural effusion requiring pleural drainage (1500-2500 mL/day). While in HNDM, the patient developed bilateral pleural effusion with increased triglycerides. A multiple-slice contrast spiral CT (TEM) of the chest showed mediastinal lymph node enlargement, bilateral pleural effusion, and the presence of fluid within the right posterior mediastinal pleura adjacent to D10-D11-D12, and an osteolytic image in D11 vertebral body. A left axillary lymph node biopsy revealed non- Hodgkin lymphoma (NHL), follicular type with large and small cells. The patient received a diet rich in medium-chain triglycerides and olive oil as a supplement, and he also received chemotherapy (dexamethasone, cyclophosphamide, doxorubicin, vincristine), being discharged after the first cycle. Chemotherapy was scheduled to be administered every 3 weeks, and drainage thoracentesis were also scheduled to be performed during his probation period. After 5 months of treatment, bilateral chylothorax disappeared.